Comparison of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio for the diagnosis of neonatal sepsis: a systematic review and meta-analysis - Lixia Bai; Peihui Gong; Xiaoyun Jia; Xinhua Zhang; Xiuhui Li; Yueqin Zhang; Hao Zhou; Yanan Kang (BMC Pediatrics, 2023)
Abstract Purpose To compare the performance of Neutrophil-to-Lymphocyte Ratio (NLR) with that of Platelet-to-Lymphocyte Ratio (PLR) in diagnosing neonatal sepsis (NS). Methods PubMed and Embase were searched for relevant studies from the inception of the databases to May, 2022. The pooled sensitivity (SEN), specificity (SPE), and area under the receiver operator characteristic curve (AUC) were measured. Results Thirteen studies involving 2610 participants were included. The SEN, SPE, and AUC of NLR were 0.76 (95%CI: 0.61–0.87), 0.82 (95%CI: 0.68–0.91), and 0.86 (95%CI: 0.83–0.89), respectively, and those of PLR were 0.82 (95%CI: 0.63–0.92), 0.80 (95%CI: 0.24–0.98), and 0.87 (95%CI: 0.83–0.89), respectively. Significant heterogeneity was observed among the studies. Subgroup analysis and meta-regression showed that types of sepsis (p = 0.01 for SEN), gold standard (p = 0.03 for SPE), and pre-set threshold (p<0.05 for SPE) might be the sources of heterogeneity for NLR, whereas the pre-set threshold (p<0.05 for SPE) might be the source of heterogeneity for PLR. Conclusions NLR and PLR would be of great accuracy for the diagnosis of NS, and the two indicators have similar diagnostic performance. However, the overall risk of bias was high, and significant heterogeneity was identified among the included studies. The results of this study should be interpreted prudently, and the normal or cut-off values and the type of sepsis should be considered. More prospective studies are needed to further support the clinical application of these findings.